Color in the Age of Impressionism Commerce, Technology, and Art. - Kalba, Laura Anne (Refiguring modernism., 2017)
"Analyzes the impact of color technologies on the visual culture of nineteenth-century France, from the early commercialization of synthetic dyes to the Lumière brothers' perfection of the autochrome color photography process. Examines the development of the basic aesthetic schemata of modern visual culture"--Provided by publisher.